Existing Analytical Frameworks for Information Behaviour Don’t Fully Explain HIV/AIDS Information Exchange in Rural Communities in Ontario, Canada. A Review of: Veinot, T., Harris, R., Bella, L., Rootman, I., & Krajnak, J. (2006). HIV/AIDS Information exchange in rural communities: Preliminary findings from a three‐province study. Canadian Journal of Information and Library Science, 30(3/4), 271‐290. - Kate Kelly (Evidence Based Library and Information Practice, 2010)
Objective – To explore and analyze, against three theoretical frameworks of information behaviours, how people with HIV/AIDS, their friends, and their family living in rural communities find information on HIV/AIDS. Design – Qualitative, individual, in‐depth, semi‐structured interviews. Setting – Two rural regions in Ontario, Canada. Subjects – Sixteen participants; 10 people with HIV/AIDS (PHAs) and 6 family members or friends. Methods – Participants were recruited through health care providers, social service agencies and through snowball sampling. Semi‐structure interviews were conducted focusing on participants’ experience with HIV/AIDS, how they find and use information on HIV/AIDS, networks for information exchange and the effect of technology on information exchange. Interviews were taped, transcribed, analyzed qualitatively using NVivo software. Results were compared to three theoretical frameworks for information behaviour: 1. purposeful information seeking (i.e., the idea that people purposefully seek information to bridge perceived knowledge gaps); 2. non‐purposeful or incidental information acquisition (i.e., the idea that people absorb information from going about daily activities); and 3. information gate keeping (i.e., the concept of private individuals who act as community links and filters for information gathering and dissemination). Main Results – Consistent with the theories: •PHAs prefer to receive information from people they have a personal relationship with, particularly their physician and especially other PHAs. •PHAs’ friends and families rely on their friends and family for information, and are particularly reliant upon the PHA in their lives. •Fear of stigma and discrimination cause some to avoid seeking information or to prefer certain sources of information, such as healthcare providers, who are bound by codes of professional conduct. •Emotional support is important in information provision and its presence supersedes the professional role of the provider (social workers and counsellors were identified as key information sources over medical professionals in this instance). Participants responded negatively to the perceived lack of support from providers including doubting the information provided. •PHAs monitor their worlds and keep up to date about HIV/AIDS.Inconsistent with theories: •Reliance on caregivers for information is not solely explained by fear of stigma or exposure. Rather, it is the specialized knowledge and immersion in HIV/AIDS which is valued. •The distinction between peer or kin sources of information and institutional information sources is less clear and relationships with professionals can turn personal over time. •Inter‐personal connections include organisations, not just individuals, particularly AIDS Service Organizations and HIV specialist clinics. •Relatively few incidents of finding useful information about HIV/AIDS incidentally were described. The concept of information just being “out there” was not really applicable to rural settings, likely due to the lack of discussion within participant communities and local media. When it was discussed, participants reported being more likely to gain misinformation through their personal networks. •Incidental information acquisition originates mostly from professional and organisational sources. Participants identified posters, leaflets, and, for those who interacted with organisations, information via mail as contributing to current awareness. •The gate keeping concept does not capture all the information sharing activities undertaken by “gate keepers” in rural areas, and neither does it include formal providers of information, yet all PHAs interviewed identified formal providers as key sources. Conclusion – The findings reinforce some of the existing analytical framework theories, particularly the importance of affective components (i.e. emotional supports) of information seeking, the presence of monitoring behaviours, and of interpersonal sources of information. However, alternate theories may need to be explored as the role of institutional information sources in the lives of PHAs doesn’t match the theoretical predication and the “gate keeper” concept doesn’t capture a significant portion of that role in rural HIV/AIDS information exchange.